You Are Hear - A Muriwai Symphony - Hay, Mette (Auckland University of Technology, 2021)
This project has grown from a previous body of work that used sound as a medium for visualising the presence of participants in the artwork. This work employed water and light to transform the visual expressiveness of sound. Sight has become the dominant human sense, with the result that unseen elements, such as sound, often pass unnoticed. This research explores ways of illuminating the invisible elements of nature through engaging in active attention. Using perceptive awareness of the moment, I will collect and make experiences and artefacts that enable me to open up a dialogue with the unseen. This dialogue will form the basis for creating an immersive experience that will allow participants to encounter and connect with dimensions of nature that go unnoticed or are hidden from the eyes.
Keywords: Listen; Her; Sound; Nature; Symphony; Invisible; Presence; Embodied; Sensorial; Senses; Kinship; Pattern